Antecedent Moisture Controls on Stream Nitrate Flux in an Agricultural Watershed. Issue 4 (1st July 2014) - Davis, Caroline A.; Ward, Adam S.; Burgin, Amy J.; Loecke, Terrance D.; Riveros‐Iregui, Diego A.; Schnoebelen, Douglas J.; Just, Craig L.; Thomas, Steven A.; Weber, Larry J.; St. Clair, Martin A.
Abstract : Evaluating nitrate‐N fluxes from agricultural landscapes is inherently complex due to the wide range of intrinsic and dynamic controlling variables. In this study, we investigate the influence of contrasting antecedent moisture conditions on nitrate‐N flux magnitude and dynamics in a single agricultural watershed on intra‐annual and rainfall‐event temporal scales. High temporal resolution discharge and nitrate concentration data were collected to evaluate nitrate‐N flux magnitude associated with wet (2009) and dry (2012) conditions. Analysis of individual rainfall events revealed a marked and consistent difference in nitrate‐N flux response attributed to wet/dry cycles. Large‐magnitude dilutions (up to 10 mg N L −1 ) persisted during the wet antecedent conditions (2009), consistent with a dominant baseflow contribution and excess groundwater release in relation to precipitation volume (discharge > > precipitation). Smaller‐magnitude concentrations (<7 mg N L −1 ) were observed during the drought conditions of 2012, consistent with a quickflow‐dominated response to rain events and infiltration/storage of precipitation resulting in discharge < precipitation. Nitrate‐N loads and yields from the watershed were much higher (up to an order of magnitude) in the wet year vs. the dry year. Our results suggest that the response of nitrate‐N loading to rain events is highly dependent on intra‐annual antecedent moisture conditions and subsurface hydrologic connectivity, which together dictate the dominant hydrologic pathways for stream recharge. Additionally, the results of our study indicate that continued pronounced wet/dry cycles may become more dominant as the short‐term driver of future nitrate‐N exports.